Emerging roles of Sox6 in the renal and cardiovascular system - Mohammad Saleem; Pierina Barturen‐Larrea; Jose A. Gomez (Physiological Reports)
Abstract The function of Sex‐determining Region Y (SRY)‐related high‐mobility‐group box (Sox) family of transcription factors in cell fate decisions during embryonic development are well‐established. Accumulating evidence indicates that the Sox family of transcription factors are fundamental in adult tissue homeostasis, regeneration, and physiology. The SoxD subfamily of genes are expressed in various cell types of different organs during embryogenesis and adulthood and have been involved in cell‐fate determination, cellular proliferation and survival, differentiation, and terminal maturation in a number of cell lineages. The dysregulation in the function of SoxD proteins (i.e. Sox5, Sox6, Sox13, and Sox23) have been implicated in different disease conditions such as chondrodysplasia, cancer, diabetes, hypertension, autoimmune diseases, osteoarthritis among others. In this minireview, we present recent developments related to the transcription factor Sox6, which is involved in a number of diseases such as diabetic nephropathy, adipogenesis, cardiomyopathy, inflammatory bowel disease, and cancer. Sox6 has been implicated in the regulation of renin expression and JG cell recruitment in mice during sodium depletion and dehydration. We provide a current perspective of Sox6 research developments in last five years, and the implications of Sox6 functions in cardiovascular physiology and disease conditions.